O impacto das fanfics na formação literária de adolescentes: uma análise sobre seu potencial na promoção da leitura - Lana, Mariana Matos de (Universidade Federal de São Carlos, 2023)
Based on the observation of Brazilian teenagers' behaviour in relation to digital culture and fan culture, this study analyses the potential of fanfics in teenagers' reading habits and their use in libraries. In order to understand whether this practice could work as a tool to promote the formation of new readers and encourage reading, we investigated its potential use and application in libraries. Specifically, the aim was to describe the concept of Fanfic and its relationship with culture; to understand the relationship between teenagers as digital natives and fan culture; to analyse the relationship between reading fanfics and the formation of new readers; and to analyse, in articles and academic papers, the strategies for using fanfics in school libraries effectively and responsibly. Through basic and exploratory research, using the qualitative method, the bibliography was surveyed throughout the year 2022, and an attempt was made to identify the main trends and gaps in the area. As a result, it was found that the literature on the subject has been published in the last 20 years and that the field of Librarianship is still lagging behind in research into Fanfics as an incentive for reading; it was also realised that the Internet is an integral part of the lives of digitally native teenagers, working in a symbiotic way and directly affecting their reading habits; it was identified that Fanfics can be a tool for encouraging reading and writing, but that they require the mediation of a specific subject.
The impact of fanfics on adolescents' literary education: an analysis of their potential in promoting reading
Keywords: Adolescentes; Leitura; Biblioteca escolar; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA